Estimation of Complement Components (C3 and C4) and hs-CRP Level in Kidney Failure Patients - Zaid N. Elia; Nisreen W. Mustafa (Polytechnic, 2019)
Several kidney diseases associated with complement activation. Complement activation occurs in progressive chronic kidney disease and may contribute to the chronic inflammation that is characteristically found in the kidney. This study was aimed to detect the level of complement system in kidney failure patients. This study was included (30) patients with renal failure and (15) healthy donors as control group. Serum samples separated from the whole blood of patients and healthy individuals. C3, C4, and high sensitive C- reactive protein (hsCRP) levels were estimated for all samples. The results were analyzed according to patients who were dialysis, non-dialysis, with diabetes, without diabetes, with high blood pressure, and without high blood pressure. The results showed that there was a significant increase (P < 0.05) in C3 level for patients with renal failure (154.12 mg/dl) compared to control group (126.08 mg/dl) while C4 level for renal failure patients (35.38 mg/dl) showed no significant change compared to control group (36.26 mg/dl). However, C3 level of patients under dialysis (152.15 mg/dl), not dialysis (162.01 mg/dl), with diabetic (155.80 mg/dl), and without diabetic (153 mg/dl) recorded significant elevation compared with control group (126.08 mg/dl) but C4 level did not show any significant change for all groups. C3 and C4 concentrations did not record significant alteration (P < 0.05) in patient with hypertension, nonhypertension, and control group. Moreover, seropositivity of CRP for patients with renal failure was ranged from 33.33% to 60% in all patients groups included in this study. hsCRP concentration significantly elevated (P < 0.05) in under dialysis (1.787 mg/L), nondialysis (1.583 mg/L), with diabetic (2.766 mg/L), nondiabetic (1.066 mg/L), with hypertension (1.84 mg/L), and nonhypertension (1.26 mg/L) when compared with control group (0.667 mg/L). The present findings suggest that the increased serum levels of C3, C4, and hs-CRP reflect the of kidney injury. Hence, this reflects the complement system as an important mediator of kidney injury and the role of anti-complement therapy in nephropathy will expand in the future.